EUS-guided gastroenterostomy vs. surgical gastrojejunostomy and enteral stenting for malignant gastric outlet obstruction: a meta-analysis - Miller, Corey; Benchaya, Joshua A; Martel, Myriam; Barkun, Alan; Wyse, Jonathan M; Ferri, Lorenzo; Chen, Yen-I (Endoscopy International Open, 2023)
Background and study aims Malignant gastric outlet obstruction (MGOO) is traditionally treated with surgical gastrojejunostomy (SGJ), which is effective but associated with high rates of morbidity, or endoscopic stenting (ES), which is less invasive but associated with significant risk of stent dysfunction and need for reintervention. Endoscopic ultrasound-guided gastroenterostomy (EUS-GE) provides a robust bypass without the invasiveness of surgery.Methods We performed a systematic review and meta-analysis comparing EUS-GE to SGJ and ES for MGOO. Electronic databases were searched from inception through February 2022. A meta-analysis was performed with results reported as odds ratios (ORs) with 95% confidence intervals (CIs) using random effects models. Primary outcomes included clinical success without recurrent GOO and adverse events (AEs).Results Sixteen studies involving 1541 patients were included. EUS-GE was associated with higher clinical success without recurrent GOO compared to ES or SGJ [OR 2.60, 95% CI1.58–4.28] and compared to ES alone [OR 5.08, 95% CI 3.42–7.55], but yielded no significant difference compared to SGJ alone [OR 1.94, 95% CI 0.97–3.88]. AE rates were significantly lower for EUS-GE compared to ES or SGJ grouped together [OR 0.34, 95% CI 0.20–0.58], or SGJ alone [OR 0.17, 95% CI 0.10–0.30] but were not significant different versus ES alone [OR 0.57, 95% CI 0.29–1.14]. Conclusions EUS-GE is the most successful approach to treating MGOO, exhibiting a lower risk of recurrent obstruction compared to ES, and fewer AEs compared to SGJ.